PHYSICAL EDUCATION IN SECONDARY EDUCATION , AN EXPERIENCE REPORT ON IFMT - CAMPUS CACERES (Fiep Bulletin - online, 2015)
In this article we seek to report an experience with high school students from the Campus IFMT Cáceres experience, identifying their perceptions of the discipline Physical Education, making a historical correlation over the teaching of physical education in Brazil, especially in high school, the changes that occurred in current pedagogical practice of teaching and learning practiced in Vocational Education. This is a qualitative research whose instruments were used, a semi - structured questionnaire, along with graduates of the Technical College in the Integrated Agricultural High School, the school year in 2010, totaling 71 students. Where we find , through the systematization of research, the discipline Physical Education , is coherently organized , the content covered in class , with the active participation of students , being thorough and pedagogically grounded , with a focus on topics of their experienced reality , end up contributing for the formation of the aspects that comprise the teaching and learning of the student .
Keywords: Vocational Education; Physical Education; Learning; teaching high school.